Ridaifen G, tamoxifen analog, is a potent anticancer drug working through a combinatorial association with multiple cellular factors. Issue 18 (15th September 2015) - Ikeda, Kentaro; Kamisuki, Shinji; Uetake, Shoko; Mizusawa, Akihito; Ota, Nozomi; Sasaki, Tatsuki; Tsukuda, Senko; Kusayanagi, Tomoe; Takakusagi, Yoichi; Morohashi, Kengo; Yamori, Takao; Dan, Shingo; et al.
Graphical abstract: Abstract: Ridaifen-G (RID-G), a tamoxifen analog that we previously synthesized, has potent growth inhibitory activity against various cancer cell lines. Tamoxifen is an anticancer drug known to act on an estrogen receptor (ER) and other proteins. However, our previous studies interestingly suggested that the mechanism of action of RID-G was different from that of tamoxifen. In order to investigate the molecular mode of action of RID-G, we developed a novel chemical genetic approach that combined a phage display screen with a statistical analysis of drug potency and gene expression profiles in thirty-nine cancer cell lines. Application of this method to RID-G revealed that three proteins, calmodulin (CaM), heterogeneous nuclear ribonucleoproteins A2/B1 (hnRNP A2/B1), and zinc finger protein 638 (ZNF638) were the candidates of direct targets of RID-G. Moreover, cell lines susceptible to RID-G show similar expression profiles of RID-G target genes. These results suggest that RID-G involves CaM, hnRNP A2/B1, and ZNF638 in its growth inhibitory activity.